Attitudes and Knowledge About Learning Disabilities: A Comparison Between Arabic- and Hebrew-Speaking University Students. (May 2019) - Shecter-Lerner, Michal; Lipka, Orly; Khouri, Marlyn
Recently, there has been a significant increase in the number of students with specific learning disabilities (SLD) in postsecondary institutions. The current study investigated attitudes toward and knowledge about SLD among students from different cultural and educational backgrounds. The study included 113 students (63 Arabic speakers and 50 Hebrew speakers) working toward bachelor's degrees in different faculties and departments at a university in northern Israel. Findings indicated that both Arabic- and Hebrew-speaking students had some knowledge regarding SLD and agreed with positive statements about SLD. However, Arabic-speaking students reported having less contact with individuals with SLD than did Hebrew-speaking students. Additionally, Arabic-speaking students reported less knowledge regarding the competence of students with SLD and were more willing to support and provide assistance to these students. Both groups revealed insufficient understanding of the essence of SLD. Implications for research and practice are discussed.